Exploration of proper heating protocol for injectable horizontal platelet-rich fibrin gel - Xijiao Zheng; Xiang Yan; Kai Cheng; Mengge Feng; Yulan Wang; Bing Xiao (SpringerOpen, 2022)
Abstract Purpose Platelet-rich fibrin (PRF) has been proposed as promising biomaterials with the advantages of host accumulation of platelets and leukocytes with entrapment of growth factors and fibrin scaffold. However, limitations including fast resorption rate (~ 2 weeks) restricts its clinical application. Recent studies have demonstrated heating treatment can prolong PRF degradation. Current published articles used the method of 75 °C for 10 min to obtain longer degradation, while few studies investigated the most suitable temperature for heating horizontal PRF. Our present study was to discover and confirm the optimum temperature for heat treatment before obtaining H-PRF gels by investigating their structure, mechanical properties, and bioactivity of the H-PRF gels after heating treatment. Methods In the present study, 2-mL upper layer of horizontal PRF was collected and heated at 45 °C, 60 °C, 75 °C, and 90 °C to heat 2-mL upper layer of horizontal PRF for 10 min before mixing with the 2-mL lower layer horizontal PRF. The weight, solidification time and the degradation properties were subsequently recorded. Scanning electron microscopy (SEM) and rheologic tests were carried out to investigate the microstructure and rheologic properties of each H-PRF gel. The biological activity of each H-PRF gel was also evaluated using live/dead staining. Results H-PRF gel prepared at 75 °C for 10 min had the fast solidification period (over a tenfold increase than control) as well as the best resistance to degradation. The number of living cells in H-PRF gel is greater than 90%. SEM showed that H-PRF gel becomes denser as the heating temperature increases, and rheologic tests also revealed that the heat treatment improved the mechanical properties of H-PRF gels when compared to non-heated control group. Future clinical studies are needed to further support the clinical application of H-PRF gels in tissue regeneration procedures. Conclusions Our results demonstrated that the H-PRF gel obtained at 75 °C for 10 min could produce a uniform, moldable gel with a short time for solidification time, great rheologic behavior and, high percent of live cells in PRF gel. A promising use of the commonly utilized PRF gel was achieved facilitating tissue regeneration and preventing degradation.